A case of primary skeletal muscle lymphoma mimicking cellulitis - Sahu, Alok (International Journal of Research in Orthopaedics, 2024)
Primary skeletal muscle lymphoma is a rare entity. Their presentation can be easily confused with a wide variety of inflammatory conditions, neoplasia as well as infectious diseases. We came across a 65-year-old lady who presented to us with complains of pain and swelling in the right thigh, leg and foot and fever-on and off for 20 days. She was initially managed elsewhere on the line of cellulitis with incision and drainage of right leg 15 days back but there had been no clinical improvement. We took her detailed history and examined her thoroughly. Relevant blood investigations were sent. However, the clinical examination findings and history were suggestive of an infective cause, blood investigations were suggestive of an acute inflammatory pathology, whereas radiological investigations (NCCT and X-ray) and cytological investigations (FNAC) which were performed at the previous place of treatment were inconclusive. We then did a CE-MRI of the right lower limb which showed centrally necrotic, enhancing mass lesion involving peroneal muscles with multiple enlarged inguinal and popliteal lymph nodes. Based on this finding, biopsy was performed and specimen was sent for histopathological examination which revealed “malignant small round cell tumor”. Immunohistochemistry was then done and tumor cells were found to be positive for vimentin, LCA, CD20 and negative for PANCK and CD3. Based on the above findings it was diagnosed as “non-hodgkin’s lymphoma (NHL) B-cell type” of right leg. Considering the confusing clinical presentation of this entity and inconclusiveness of blood and basic radiological investigations, lesions of extremities presenting with features of cellulitis must be carefully assessed.